The relationship between musculoskeletal disorders and mental workload among female computer workers at services sector in Shah Alam / Muhammad Mohd Said - Muhammad, Mohd Said (2021)
This study conducted to determine the relationship between musculoskeletal disorder and mental workload among female computer workers. This study conducted on sixty (60) female computer workers at services sector in Shah Alam. An assessment method to determine the ergonomic risk level for the workstation is using the ROSA tool. The questionnaire distributed is concerning the demographic data of respondents. The assessment of level musculoskeletal disorders was assessed using the Cornell Musculoskeletal Discomfort questionnaire. The mental workload level was evaluated using Carmen-Q and NASA-TLX. The level of mental health is assessed using DASS-21. The data were analyzed using SPSS version 20.0. The level of ergonomic risk for workstation obtained is 5.54. 50% staff experience a severe level of musculoskeletal disorders with majority of the workers experience discomfort at the lower back (13.5%), neck (12.4%), and right shoulder (9.7%). For the hand region, the data showed respondents are experienced discomfort at area A (11.96%), area B right (9.96%), and at area E right (9.96%). NASA-TLX index showed that the subject assessed that Effort Demand is the highest segment with 64.08%, Temporal Demand (63.67%). DASS-21 showed that most subjects have mental stress issues, with a percentage of 81.7%. For the segment of DASS21 that symptomize, anxiety held at the highest rate followed by depression in the 2nd place, with 15% of the respondents felt mild. Pearson Correlation statistically showed a significant correlation between the total score of: Weighted Workloads and total score for the MSDS body region, a few part of MSDS body region with a few segment under mental workload score, total score of Weighted Workload with MSDS right-hand, and MSDS hand left.